Inadvertent hypothermia in paediatric radiotherapy practices under sedation: a single centre observational study - Aytac, Ismail; Guven Aytac, Betul; Ozturk, Huseyin Furkan (Journal of the Pakistan Medical Association, 2023)
Objective: To detect changes in body temperature during outpatient procedures and to identify factors associated with hypothermia in the paediatric population undergoing radiotherapy under sedation. Method: The observational study was conducted between July and October 2022 at Ankara City Hospital, Turkey, and comprised paediatric cancer patients aged from 1 month to 18 years who needed sedation or general anaesthesia during radiotherapy. Baseline body temperature T1 was measured before transportation to the radiotherapy room, while body temperature T2 was taken after radiotherapy. Data was analysed using SPSS 20. Results: A total of 152 radiotherapy sessions related to 13 children were evaluated. There were 8(61%) boys and 5(38%) girls with overall mean 4.46±3.45 years (range: 2-13 years). The mean body surface area as 0.70±0.212. Radiotherapy was performed in 9(69%) patients, while 4(31%) patients underwent tomotheraphy. The dose used was 180cGy in 12(92.3%) patients. Hypothermia was observed in at least one session in 12(92.3%) patients. There was significant difference in body temperature at baseline and post-radiotherapy (p<0.05). Conclusion: There were significant changes in body temperature during outpatient procedures in the paediatric population undergoing radiotherapy under sedation. Key Words: Anaesthesia recovery period, Hypothermia, Paediatrics, Radiotherapy.